Peliputan Langsung Persidangan Pidana: Harmonisasi KUHAP dan Undang-Undang Pers - Kanda Reza Pahlevi Tetuko Mozaik Romadhona; Indriati Amarini (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the legal implications of live coverage of criminal trials within the framework of the Indonesian Criminal Procedure Code (KUHAP) and Law Number 40 of 1999 on the Press, as well as to formulate a harmonization model to balance judicial transparency and fair trial principles. This research employs a normative juridical method with statutory and conceptual approaches, analyzed qualitatively through relevant legal norms and doctrines. The findings indicate that live coverage cannot be interpreted as an absolute manifestation of open court proceedings, but rather as an extension of public access to information that must be proportionally limited to safeguard the presumption of innocence, evidentiary integrity, and judicial independence. The absence of clear technical regulations in KUHAP regarding live broadcasting has created disharmony with the press law regime and poses risks such as trial by media, witness contamination, and undue pressure on the judiciary. The novelty of this research lies in its integrative approach that simultaneously examines KUHAP and the Press Law within a unified normative-operational harmonization framework. Its contribution is the formulation of a collaborative regulatory model between the Supreme Court and the Press Council, including selective broadcasting restrictions, delayed broadcasting mechanisms, pool feed systems, and strengthened journalistic ethics to ensure a balanced relationship between judicial transparency and substantive justice. Penelitian ini bertujuan untuk menganalisis implikasi hukum peliputan langsung persidangan pidana dalam perspektif Kitab Undang-Undang Hukum Acara Pidana (KUHAP) dan Undang-Undang Nomor 40 Tahun 1999 tentang Pers, serta merumuskan model harmonisasi guna menyeimbangkan keterbukaan peradilan dengan prinsip fair trial. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual yang dianalisis secara kualitatif terhadap norma hukum dan doktrin yang relevan. Hasil penelitian menunjukkan bahwa peliputan langsung tidak dapat dimaknai sebagai perwujudan absolut asas persidangan terbuka untuk umum, melainkan sebagai bentuk perluasan akses informasi yang harus dibatasi secara proporsional untuk melindungi asas praduga tidak bersalah, integritas pembuktian, dan independensi hakim. Kekosongan pengaturan teknis dalam KUHAP terkait peliputan langsung menimbulkan disharmonisasi dengan rezim kebebasan pers serta berpotensi memicu trial by media, kontaminasi kesaksian, dan tekanan terhadap proses peradilan. Kebaruan penelitian ini terletak pada pendekatan integratif yang mengkaji secara simultan hubungan antara KUHAP dan Undang-Undang Pers dalam kerangka harmonisasi normatif dan operasional. Kontribusi penelitian ini adalah merumuskan model regulasi kolaboratif antara Mahkamah Agung dan Dewan Pers melalui pembatasan siaran selektif, mekanisme delayed broadcast, sistem pool feed, serta penguatan etika jurnalistik untuk menjamin keseimbangan antara transparansi peradilan dan perlindungan keadilan substantif.